2021
DOI: 10.1088/1755-1315/939/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Temperature of Components of Cotton-Raw Material in a Drum Dryer with a Constant

Abstract: This article solves one parabolic-type boundary value problem for determining the heat-moisture state of raw cotton in drum dryers at a constant air temperature. Numerical results are obtained by the Bubnov – Galerkin method of the problem under consideration, a comparative analysis is carried out with experimental data. It is shown that the proposed mathematical model and its numerical algorithm adequately describe the drying process of raw cotton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…3, a) resistant to fire and high temperature, as well as basalt roving in sock weaving machines, as well as elastane, polyamide, polyester yarns are produced in various options sleeve of knitted fabric (Fig. 3, b) were taken [12].…”
Section: Resultsmentioning
confidence: 99%
“…3, a) resistant to fire and high temperature, as well as basalt roving in sock weaving machines, as well as elastane, polyamide, polyester yarns are produced in various options sleeve of knitted fabric (Fig. 3, b) were taken [12].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, in the process of cleaning cotton, it is carried out with the help of fingers made of elastic material installed on the drum (Fig. 1) [7].…”
Section: Experimental Devicesmentioning
confidence: 99%
“…If the speed of the air flow is further reduced, then after 18 m/s the particles of fibrous materials fall to the bottom of the pipe and move unevenly, bouncing. The results of monitoring the process of air transportation of fibrous materials showed that the raw materials are unevenly transferred to the pipes of pneumatic transport [5][6][7]. As a result, the cotton moves in separate sections in the pipe, somewhere concentrated, and somewhere in a rarefied state.…”
Section: Introductionmentioning
confidence: 99%